2020
DOI: 10.1007/s10681-020-02599-6
|View full text |Cite
|
Sign up to set email alerts
|

QTL and candidate gene analyses of rootstock-mediated tomato fruit yield and quality traits under low iron stress

Abstract: QTL and candidate gene analyses of rootstock-mediated tomato fruit yield and quality traits under low iron stress. Euphytica, 216(4), 1-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
4
8
0
Order By: Relevance
“…Aside from the fact that the wild parent S. elaeagnifolium is a species that grows in poor environments where the N is low [16,18], the evaluation of the advanced backcrosses allowed us to determine genetic parameters of great relevance for important traits in eggplant breeding, including the detection of putative QTLs for some of them. Similar studies were published on QTL detection in tomato under abiotic stress conditions [69,70] but not under low N conditions.…”
Section: Discussionsupporting
confidence: 77%
“…Aside from the fact that the wild parent S. elaeagnifolium is a species that grows in poor environments where the N is low [16,18], the evaluation of the advanced backcrosses allowed us to determine genetic parameters of great relevance for important traits in eggplant breeding, including the detection of putative QTLs for some of them. Similar studies were published on QTL detection in tomato under abiotic stress conditions [69,70] but not under low N conditions.…”
Section: Discussionsupporting
confidence: 77%
“…Note that the increasing allele (the allele increasing the trait mean) at those QTLs (except for FlN_WD_4.2 within cluster V) was from S. lycopersicum , however, due to the epistatic interactions detected for ShDW and ShWC under water deficit, the best (increasing) genotype is conditioned to the presence of a S. pimpinellifolium allele at a second locus ( Figure S2 ). In the case of ShDW_WD_3 (cluster III), this locus at SNP 1495 corresponds to a previously reported QTL for iron concentrations in leaf and fruit under low iron availability (Fe_F/L_12 in [ 50 ]), in agreement with the known effect of drought on plant nutrient acquisition [ 27 , 38 ]. These results suggest the importance of considering epistatic interactions regarding marker-assisted selection when using wild germplasm.…”
Section: Discussionsupporting
confidence: 84%
“…Very few QTLs were detected for the xylem concentration of nutrients in well-watered plants ( Table 2 ): 3 for B, 1 for Mg, 1 for Na, and 2 for Sr. Except for that of Na (Na_C_7) at the same position as Na_WD_7, which must correspond to the Na transporter HKT1 (as found in previous studies using this RIL population; [ 46 , 50 , 51 ]), no other was detected under water stress. Interestingly, xylem concentrations of some nutrients (Mn, Mg, Ca, Sr, Zn, P, and S) were associated under both watering regimes as visualized in the principal component analysis ( Figure 2 , Table S3 ), but the clustering of QTLs controlling these traits (QTL clusters II, IV, VI, VII, VIII, and XI in Table S4 ), genetically supporting such association, was only detected under water deficit.…”
Section: Discussionsupporting
confidence: 56%
“…A recent study in tomato identified 103 QTLs, out of which six QTLs were for fruit and leaf Fe contents while eight QTLs were for yield Fe content (FeUEc). Also, two relevant candidate genes encoding for specific proteins of tomato xylem sap were identified under Fe deficiency, thus affecting fruit yield and quality traits ( Asins et al, 2020 ). Eight QTLs were detected for Al resistance in common bean ( Phaseolus vulgaris ) with a phenotypic variation of 7.6–14.7%.…”
Section: Seven-(omics)-based Approaches To Improve Toxic Metals/metalloids Tolerance In Plantsmentioning
confidence: 99%